A Case of Waterhouse-Friderichsen Syndrome Resulting from an Invasive Pneumococcal Infection in a Patient with a Hypoplastic Spleen - Kazumasa Emori; Nobuhiro Takeuchi; Junichi Soneda (Case Reports in Critical Care)
A 50-year-old male was brought to our emergency department by ambulance with complaints of pain and numbness in both legs. At arrival, purple spots were evident on his neck and face. Examination of the vital sign indicated septic shock. Laboratory data and blood gas analysis revealed disseminated intravascular coagulation, multiple organ failure, and metabolic acidosis. Peripheral blood smears revealed Howell-Jolly bodies, indicating decreased splenic function. A rapid urinary pneumococcal antigen test was also found to be positive. After admission to the intensive care unit, extensive treatment, including polymyxin-B direct hemoperfusion and administration of methylprednisolone and broad spectrum antibiotics was immediately initiated. Despite of our efforts to save his life, the patient died six hours after the arrival. The following day, blood cultures revealed the presence of Streptococcus pneumoniae. An autopsy revealed a hypoplastic spleen and a bilateral adrenal hemorrhage, indicating acute adrenal insufficiency caused by sepsis. Finally, the patient was diagnosed with Waterhouse-Friderichsen syndrome. Although severe infection may be seen in the splenectomized patients, it should be noted that patients with a hypoplastic spleen may have acute severe infections. We, therefore, report a case of Waterhouse-Friderichsen syndrome resulting from an invasive pneumococcal infection in a patient with a hypoplastic spleen.